Sistem Perbankan Syari’ah dan Konvensional Dalam Perspektif Al-Qur’an (Studi Pada Praktek Sewa Menyewa) - Muzakkir S.; Humam Balya (TAFAQQUH, 2023)
This study aims to analyze the practice of leasing (ijarah) in Islamic and conventional banking systems based on the Qur'anic perspective, and to identify the differences in principles and operations between these two banking systems. The research employs a descriptive qualitative approach by analyzing Qur'anic verses related to leasing concepts and comparing financing practices in Islamic and conventional banks. The study identifies two critical assessments of conventional leasing practices according to Islamic principles: the imposition of rental fees from the beginning of the contract and the transfer of all risks to the lessee, especially regarding the residual value of assets. The leasing principles in the Qur'an remain relevant as a legal foundation for contemporary economics. Operationally, the main difference between Islamic and conventional banks lies in terminology and the ujroh payment system that complies with Islamic principles. This study contributes to understanding the implementation of Islamic principles in leasing financing products and serves as a reference for developing Islamic banking products that are more compliant with sharia provisions.